The effect of athletics and football training characteristics on some respiratory parameters in female athletes - Fatih Bilici; Ömer Faruk Bilici; Sedat Okut; Muhammed Zahit Kahraman; Cengizhan Sarı (Turkish Journal of Kinesiology, 2023)
The aim of this research is to examine the effect of training characteristics specific to athletics and football branches on some respiratory parameters in female athletes. 15 female long-distance runners (age: 18.86 ± 1.18 years), 15 female football players (age: 20.40 ± 1.24 years), and 15 female sedentary (age: 20.26 ± 2.05 years) participated voluntarily in the study. The respiratory function values of the participants were determined using a spirometer device. A one-way ANOVA test was applied to compare the mean of respiratory parameters between groups. Tukey post-hoc test was used to determine which group caused the difference in cases where there was a significant difference. In the research findings, the forced vital capacity (FVC), the volume of air exhaled in the first second of forced expiration (FEV1), the volume of air exited in the first second/forced vital capacity (FEV1/FVC), peak expiratory flow rate (PEF), forced expiratory flow between 25% and 75% of vital capacity (FEF25-75%), vital capacity (VC) and maximal voluntary ventilation (MVV) values of the long-distance runners were statistically significantly higher than the sedentary (p